Writing to Trees with the Trees : Experiments in NIROX and Mustarinda - Arlander, Annette (Routledge, 2024)
This text deals with forests and fences in a material sense, taking as its starting point two experiments related to the problem of how to perform with trees in two residencies on opposite sides of the planet: An ARA (Arts Research Africa) residency in Johannesburg during February–March 2020, including a short stay in NIROX, Krugersdorp; and a residency in Mustarinda near Hyrynsalmi, Kainuu, in northeastern Finland in September 2020. Here I focus on attempts at performing with trees by writing letters to them in both of these locations, as part of the project Meetings with Remarkable and Unremarkable Trees (2020–21). As a reminder of the many ways to understand the idea of forest, I insert some quotes from a play written by Heiner Müller in 1972 as intermissions between the sections of the text. Writing letters in the presence of the tree that is being addressed, opening the possibility of being addressed by the tree as well, is more like a gesture of respect rather than an attempt at direct communication.
Keywords: metsät; luonto; luonnonsuojelualueet; luontosuhde; puut (kasvit); kuvateokset; luonnonsuojelu; taiteellinen tutkimus